TRAIL attenuates the development of atherosclerosis in apolipoprotein E deficient mice - Watt, Victoria (Elsevier, 2011)
TRAIL (tumour necrosis factor-related apoptosis inducing ligand) is most often reported to induce apoptosis in tumour cells. It is expressed in artery walls but its role and regulation in vascular pathologies is little studied. We aimed to measure the effect of genetic deletion of TRAIL on atherosclerosis in a mouse model. TRAIL was mainly expressed in endothelium, smooth muscle cells and macrophages within plaques. The absence of TRAIL in chow and in fat-fed mice led to greater lesion coverage in aortae (8 weeks, % area ± SEM), n = 7–8, 1.24 ± 0.2 (no TRAIL, chow diet) vs. 0.42 ± 0.1, p < 0.01 and 3.4 ± 0.8 (no TRAIL, Western diet) vs. 0.94 ± 0.2, p < 0.01 and larger, smooth muscle cell rich lesions at aortic roots than control mice (8 weeks, mean lesion area/total cross sectional area ± SEM, n = 7–8, 0.17 ± 0.01 (no TRAIL, chow diet) vs. 0.135 ± 0.006, p < 0.05 and 0.36 ± 0.03 (no TRAIL, Western diet) vs. 0.23 ± 0.02, p < 0.05) particularly at early time points. The larger early lesions appeared to be as a result of increased smooth muscle cells in lesions of TRAIL deficient, pro-atherosclerotic animals. We conclude that TRAIL attenuates plaque size at early stages of atherosclerosis.